2018
DOI: 10.12816/0044533
|View full text |Cite
|
Sign up to set email alerts
|

Level of Chemerin and Anti-Müllerian Hormone in Egyptian Obese Women with Polycystic Ovarian Syndrome

Abstract: Background: Chemerin is a newly discovered adipokine that regulates adipocyte development, metabolic function as well as immune function. Anti-Müllerian hormone (AMH) is a dimeric glycoprotein that belongs to the transforming growth factor-beta family. Aim of the study: was to evaluate the serum levels of Chemerin and AMH in one trial to show their possible involvement in the pathogenesis of PCOS and their association with obesity. Subjects and methods: This study was performed on eighty subjects divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…PCOS groups showed significant increase in TC, TAG, LDL-C and significant decrease in HDL-C in obese women when compared to the non-obese women, similar results were found in studies done by Foda et al 3 Regarding the hormonal profile the present results revealed significant increases in serum LH and total testosterone levels and no significant differences in serum FSH and progesterone levels between PCOS patients compared with control subjects. These results are in agreeing with Hasan and El Hameed, Sun et al and El Omda et al 10,21,22 . Coutinho and Kauffman reported that in the polycystic ovary syndrome LH pulse frequency and amplitude are higher throughout the menstrual cycle in comparison to that observed in healthy women 23 .…”
Section: As Shown Insupporting
confidence: 91%
“…PCOS groups showed significant increase in TC, TAG, LDL-C and significant decrease in HDL-C in obese women when compared to the non-obese women, similar results were found in studies done by Foda et al 3 Regarding the hormonal profile the present results revealed significant increases in serum LH and total testosterone levels and no significant differences in serum FSH and progesterone levels between PCOS patients compared with control subjects. These results are in agreeing with Hasan and El Hameed, Sun et al and El Omda et al 10,21,22 . Coutinho and Kauffman reported that in the polycystic ovary syndrome LH pulse frequency and amplitude are higher throughout the menstrual cycle in comparison to that observed in healthy women 23 .…”
Section: As Shown Insupporting
confidence: 91%
“…In total, serum and FF chemerin levels were measured in nineteen 16‐18,32,33,35‐48 and four studies, 10,18,34,49 respectively. The methods of assessing serum and FF chemerin levels were ELISA 10,16‐18,32‐48 or Wb 49 .…”
Section: Resultsmentioning
confidence: 99%
“…In total, serum and FF chemerin levels were measured in nineteen 16‐18,32,33,35‐48 and four studies, 10,18,34,49 respectively. The methods of assessing serum and FF chemerin levels were ELISA 10,16‐18,32‐48 or Wb 49 . However, in total, five studies assessed chemerin mRNA expression in the subcutaneous and omental adipose tissues 17,32 and ovarian (granulosa cells in follicular fluid) 10,18,34 using reverse transcription‐polymerase chain reaction (RT‐PCR), due to the lack of data, only ovarian chemerin mRNA expression was analysed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations